Issues on privatisation : the telecommunication industry. - Chia, Michelle Hwee Lin. (2013)
The globalisation of businesses, the deregulation of the world’s international markets and the rapid development of technology have led to a greater demand for good telecommunication facilities. Many countries have chosen to cope with these changes by introducing competition into their once rigid and monopolistic telecommunication industries. This paper explores the international telecommunications revolution and how it has affected the Singapore telecommunications industry.